Respuesta :

We can find the x and y-intercept by substituting zero for x and y respectively.Part A

iven the eequation below;

[tex]y=x+7[/tex]

When x=0

[tex]\begin{gathered} y=0+7 \\ y=7 \end{gathered}[/tex]

when y=0

[tex]\begin{gathered} 0=x+7 \\ x=-7 \end{gathered}[/tex]

Answer 1

[tex]\begin{gathered} x-\text{intercept}=(-7,0) \\ y-\text{intercept}=(0,7) \end{gathered}[/tex]

Part B

[tex]y=x^2-3[/tex]

When x=0

[tex]\begin{gathered} y=0^2-3 \\ y=-3 \end{gathered}[/tex]

When y=0

[tex]\begin{gathered} 0=x^2-3 \\ x^2=3 \\ x=\pm\sqrt[]{3} \\ x=-\sqrt[]{3}\text{ or x=}\sqrt[]{3} \end{gathered}[/tex]

Answer 2:

[tex]\begin{gathered} x-\text{intercept}=(-\sqrt[]{3},0) \\ x-\text{intercept}=(\sqrt[]{3},0) \\ y-\text{intercept}=(0,-3) \end{gathered}[/tex]